(untitled) (INNOVATIVE ECONOMY, 2020)
Mayovets Ya.M. RESEARCH OF EFFICIENCY OF INNOVATIVE DEVELOPMENT OF AGRARIAN ENTREPRENEURSHIP IN UKRAINE Purpose. The aim of the article is to explore the current state and determine the directions of innovative development of the agrarian economy of Ukraine; to identify the factors that provide the effectiveness of innovative measures with the help of taxonomic analysis method. Methodology of research. The methodological basis of a scientific article is a set of methods and techniques of scientific analysis, in particular methods of analysis and synthesis, unity of historical and logical, comparison, statistical and graphical methods. Using the method of taxonomic analysis has allowed to reveal the degree of innovation of modern agrarian entrepreneurship in Ukraine. Findings. It has been established that efficiency is the ultimate goal of the agrarian business sector. It is determined that if as a result of the use of innovations production is increased, this confirms its efficiency and vice versa. The thesis is based on the fact that the growth of production is always connected with the use of a certain combination of the existing innovative tool, in particular: technology and resource-saving technologies, production structures, personnel capable of creative innovative thinking, improved management and organizational methods and techniques, etc. It is concluded that the synergy effect of the use of innovative components will be greater than the simple arithmetic sum of its individual parts. The existing discussions in the Ukrainian economic sciences on the impact on the effectiveness of the agro-producer are insignificant, at first glance, but significant in relation to the impact on the final result of agrarian business of innovative measures: storage of agricultural products, timing of implementation, logistics, etc. Increasing the efficiency of existing resource potential is considered as a factor in strategic opportunities for increasing the competitiveness of enterprises. The role of innovations in the development of agrarian entrepreneurship in Ukraine is explored. The attention is drawn to possible negative side effects associated with the desire of agricultural producers to achieve a higher level of efficiency. On the example of the production of genetically modified agricultural products, a contradiction in the innovative development of domestic agricultural business is traced. The attention is paid to strengthening the influence of organizational and managerial innovations on increasing the efficiency of agrarian entrepreneurship. It is pointed out the importance of moving the center of gravity of innovation management from the production stage to the design stage, which minimizes unpredictable costs. The differences in determining the effectiveness of innovative measures in various spheres of agricultural production are analyzed. Particular attention is paid to his dependence on technical, technological and organizational and economic innovations. Originality. The scientific novelty of the research results is that the effectiveness of innovation in the agrarian sector of Ukraine is analyzed on the basis of the taxonomic analysis method. Its advantage is the use of multidimensional economic objects, which are described by a large spectrum of indicators. This allowed streamlining the multidimensionality of such a category as the innovative development of agrarian entrepreneurship relative to the standard vector of the standard. Practical value. The analysis of the dynamics of indicators of the development of farms in the Lviv region allowed revealing the degree of their innovation and taking into account the identified trends in practical activities. Key words: innovative tools; innovative potential; efficiency; forms of management; organizational and managerial innovations; method of taxonomic analysis.